Genetic Diversity Revealed among Rattan Species of Andaman and Nicobar Islands, India - Jaisankar, I.; Velmurugan, A. (Indian Forester, 2018)
The aim of the present study was to investigate the molecular characterization of rattans naturally grown in the different parts of Andaman and Nicobar Islands using Restricted amplified polymorphic DNA (RAPD) and Inter simple sequence repeat (ISSR) techniques. PCR amplifications with 8 RAPD primers gave an average of 7.37 selected markers/primers, with a maximum of 10 (OPA-4) and minimum of 6 (OPE-02 and OPE-06). Percentage of polymorphic bands ranged from 50 - 70% in RAPD primers. Among 59 selected bands 36 (61.0) were polymorphic. The amplification with seven ISSR primers generated 53 bands and 30 (56.60 %) were polymorphic. The highest polymorphism was observed in OPA -7 (75%) in RAPD and IS16 (71.45%) in ISSR. RAPD primers recorded more polymorphism as compare to ISSR primers. The overall average polymorphism of 12 accessions using 15 primers was 58.92 %.The present study revealed the higher genetic divergence among rattans and hence, the rattans from Andaman and Nicobar are unique which could be useful for breeding programmes to develop the new superior genotypes/ cultivar as well as those accessions needs attention for conservation and subsequent utilization.